Pengaruh Metode Brain Gym terhadap Peningkatan Kemampuan Menyimak Anak Kelompok B Di TK Buah Hati Ujungpangkah Gresik - Alfi Hikmawati (Journal of Islamic Education for Early Childhood, 2022)
Listening is the same as defending what people say. To be able to improve listening skills, children must respond well through their learning activities. Through learning by using the brain gym method, children can improve their listening skill optimally. Based on the first observation with the tutors in “Buah Hati” kidergarten Ujungpangkah Gresik, there were 30 % of the 15 child had problem in listening and understanding what the teacher said, doing eye contact when the teacher give the information, listening to stories and understand image, retelling the short story, expressing their opinion, answering a simple question, repeating the words that they have heard, repeating of the a songs, when the teacher just used the student workactivity in the learning process without any variation of learning media. The events that occurred in this research area became the background for researchers to determine the effect of the Brain Gym on improving the listening ability of children in group B at TK Buah Hati Ujungpangkah Gresik. This research uses a pre-experimental research design with the type of one-group pretest-posttest design. The subject of this study is 15 kindergarden student for about child B group “Buah Hati”. The method of the data collection is observation of participate. The analysis technique of this researching using non-parametric analysis technique which use the test Wilcoxon matched pairs test. Based on the results of the study, it can be concluded that the Brain Gym method has an effect on increasing the listening ability of group B children in Tk Buah Hati Ujungpangkah Gresik by looking at the analysis of the results Zhitung<Ztabel (received).